Meningkatkan Nilai Perusahaan: Peran Pertumbuhan Penjualan dan Kepemilikan Manajerial dengan Ukuran Perusahaan sebagai Faktor Moderasi - Sevty Wahiddirani Saputri; Rakhmawati Oktavianna; Benarda Benarda; Lulu Septia Rahmadani; Zihan Nurhaliza (Jurnal Liabilitas, 2026)
This study examines and analyzes the effects of sales growth and managerial ownership on firm value in non-cyclical customer companies. This study used panel data consisting of 90 samples from 2020 to 2024. The findings indicate that sales growth negatively impacts firm value, but managerial ownership has no effect on firm value. Firm size moderates the relationship between sales growth and firm value but does not moderate the relationship between managerial ownership and firm value. This is likely because increased sales growth is not necessarily accompanied by an increase in the company's net profit. One possible cause is increased operational costs and high taxes. In managerial ownership, management, acting as an agent, is trusted by shareholders to manage the company to achieve its goals and ensure the welfare of the principal. However, agents do not always act according to the principal's wishes, as agents engage in opportunistic behavior.